2021
DOI: 10.1051/0004-6361/202039918
|View full text |Cite
|
Sign up to set email alerts
|

The double signature of local cosmic-ray acceleration in star-forming regions

Abstract: Context. Recently, there has been an increased interest in the study of the generation of low-energy cosmic rays (< 1 TeV) in shocks situated on the surface of a protostar or along protostellar jets. These locally accelerated cosmic rays offer an attractive explanation for the high levels of non-thermal emission and ionisation rates observed close to these sources. Aims. The high ionisation rate observed in some protostellar sources is generally attributed to shock-generated UV photons. The aim of this arti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…The spread of ζ ion in dense cores (Caselli et al 1998) is supposed to be related to uncertainties in the chemical network, in the depletion process of elements such as carbon and oxygen, as well as because of the presence of tangled magnetic fields (Padovani & Galli 2011;Padovani et al 2013;Silsbee et al 2018). We note that the models presented here only account for the propagation of interstellar CRs, but in more evolved sources, such as in high-mass star-forming regions and hot cores, there could be a substantial contribution from locally accelerated charged particles (Padovani et al 2015(Padovani et al , 2016Gaches & Offner 2018;Padovani et al 2021b). (Caselli et al 1998), empty hexagons (Bialy et al 2022), an empty circle (Maret & Bergin 2007), and an empty pentagon (Fuente et al 2016).…”
Section: Appendix C: Cosmic-ray Ionisation Rate Estimates: Update Fro...mentioning
confidence: 96%
See 1 more Smart Citation
“…The spread of ζ ion in dense cores (Caselli et al 1998) is supposed to be related to uncertainties in the chemical network, in the depletion process of elements such as carbon and oxygen, as well as because of the presence of tangled magnetic fields (Padovani & Galli 2011;Padovani et al 2013;Silsbee et al 2018). We note that the models presented here only account for the propagation of interstellar CRs, but in more evolved sources, such as in high-mass star-forming regions and hot cores, there could be a substantial contribution from locally accelerated charged particles (Padovani et al 2015(Padovani et al , 2016Gaches & Offner 2018;Padovani et al 2021b). (Caselli et al 1998), empty hexagons (Bialy et al 2022), an empty circle (Maret & Bergin 2007), and an empty pentagon (Fuente et al 2016).…”
Section: Appendix C: Cosmic-ray Ionisation Rate Estimates: Update Fro...mentioning
confidence: 96%
“…Hollenbach & McKee 1989;Karska et al 2018). However, in the same shocks, for example along a protostellar jet or on the surface of a protostar, it is also possible to locally accelerate CRs (Padovani et al 2015(Padovani et al , 2016(Padovani et al , 2021bGaches & Offner 2018), and therefore even more intense H 2 lines should be observed. Consequently, this technique could also be used to further confirm the enhanced ionisation triggered by local CRs expected in star-forming regions.…”
Section: A Look-up Plot For ζ Ion and αmentioning
confidence: 99%
“…The spread of ζ ion in dense cores (Caselli et al 1998) is supposed to be related to uncertainties in the chemical network, in the depletion process of elements such as carbon and oxygen, as well as because of the presence of tangled magnetic fields (Padovani & Galli 2011;Padovani et al 2013;Silsbee et al 2018). We note that the models presented here only account for the propagation of interstellar CRs, but in more evolved sources, such as in high-mass star-forming regions and hot cores, there could be a substantial contribution from locally accelerated charged particles (Padovani et al 2015(Padovani et al , 2016Gaches & Offner 2018;Padovani et al 2021b).…”
Section: Appendix A: Energy Loss Function For Electrons In Heliummentioning
confidence: 96%
“…However, in the same shocks, e.g. along a protostellar jet or on the surface of a protostar, it is also possible to locally accelerate CRs (Padovani et al 2015(Padovani et al , 2016Gaches & Offner 2018;Padovani et al 2021b), and therefore even more intense H 2 lines should be observed. Consequently, this technique could also be used to further confirm the enhanced ionisation triggered by local CRs expected in star-forming regions.…”
Section: A Look-up Plot For ζ Ion and αmentioning
confidence: 99%
“…The observations of Cabedo et al (2022) also show the CRs ionization rate is increasing at small envelope radii, toward the central protostellar embryo. Several theoretical works have investigated the role of shocks at the protostellar surface and magnetic mirroring within the jets as efficient forges to accelerate locally low-energy cosmic rays, and their role in increasing the ionization rate of the shielded protostellar material (Padovani et al, 2015;Silsbee et al, 2018;Fitz Axen et al, 2021;Padovani et al, 2021). In B335, it seems that local acceleration of CRs, and not the penetration of interstellar CRs, may be responsible for the gas ionization at small envelope radii.…”
Section: Fraction Of Ionized Gasmentioning
confidence: 99%